The impact of Limosilactobacillus reuteri in combination with non-surgical periodontal therapy on periodontal clinical parameters and salivary and subgingival microbiota composition in individuals with stage III–IV periodontitis: a randomized controlled trial - Pengcheng Huo; Li Deng; Jiawei Lu; Powen Kan; Rui Jing; Li-jun Luo (BMC Oral Health)
Abstract Background The clinical and microbiological outcomes of probiotic-assisted periodontal therapy remain inconclusive in prior research. This ambiguity may stem from uncertainties regarding the duration, dosage, and administration route of probiotics. Additionally, earlier studies predominantly concentrated on the identification of individual bacterial species, thereby limiting the ability to thoroughly elucidate the intricate composition of microbial communities and the synergistic or antagonistic interactions among their constituents. The study aimed to investigate the effect of combining probiotics with non-surgical periodontal therapy on clinical and microbiota changes in patients with stage III–IV periodontitis. Methods A total of 40 patients were randomized into two groups to receive non-surgical periodontal treatment. The test group received Limosilactobacillus reuteri for 21 days along with treatment. Periodontal indicators were examined at baseline and 1 and 6 months after treatment. Saliva and subgingival biofilm samples were collected for 16 S rRNA gene sequencing analysis. Results After treatment, both groups showed significant improvements in clinical parameters. In the test group, attachment loss and the medium pocket were significantly reduced at 6 months compared to that at 1 month. The presence of Tannerella forsythia in subgingival biofilms decreased significantly in the test group after treatment. Among salivary microorganisms, the abundance of Prevotella nanceiensis significantly increased in both groups, while that of Streptococcus sp. was significantly reduced in the control group. Linear discriminant analysis indicated that the most significant distinction between the groups was observed in the subgingival biofilm samples 1 month after treatment. Conclusions Combining L. reuteri with non-surgical periodontal therapy may not directly improve clinical indicators. The treatment showed potential benefits by changing the microbial composition of subgingival biofilm and enhancing treatment sensitivity. Trial registration The trial was approved by the Chinese Clinical Trial Registry (ChiCTR) on March 25, 2021, with registration number ChiCTR2100044638.